Geraniol ameliorates testicular damage in diabetic rats via inhibition of redox parameters and mitochondrial-mediated apoptosis - Tolulope A. Oyedeji; Holiness SA. Olasore; Abimbola K. Oluwole-Banjo; Josiah A. Isong; Blessing O. David; Comfort Ekpere; Omofolarin O. Ilesanmi; Daniella G. Madu; Clementina Matthew (Elsevier, 2023)
Background: Diabetes is a disease characterized by high levels of reactive oxygen species that trigger a series of events that culminate in programmed cell death. Terpenoids from plants used in traditional Chinese medicine have preventive and therapeutic potential. However, it is not known if geraniol, a monoterpene will prevent testicular damage in diabetic rats. Thus, this study investigated the antioxidant, and antiapoptotic effects of geraniol on testicular damage in diabetic male Wistar rats. Also, the interactions between geraniol with rat liver F1 ATPase and oxidized rat cytochrome c were investigated. Methods: A single intraperitoneal dose of streptozotocin (60 mg/kg) was used to induce diabetes in rats. Male Wistar rats were divided into 4 groups - CT (control), DA (Diabetic, 60 mg/kg streptozotocin), GE (Geraniol-treated, 60 mg/kg streptozotocin + 200 mg/kg geraniol), and GL (Glibenclamide-treated, 60 mg/kg streptozotocin + 5 mg/kg Glibenclamide). Rats were sacrificed by cervical dislocation under anesthesia after 21 days of treatment. Testicular superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), cytochrome c, caspase 9 and caspase 3, and testosterone (testes and plasma) were determined spectrophotometrically. The interactions between geraniol, and glibenclamide, with rat liver F1-ATPase (1MAB) and oxidized rat cytochrome c (5FD4) were assessed by molecular docking. Results: The results showed that SOD, and CAT levels were significantly (p<0.05) lowered in the DA group. Significant increases in SOD, CAT, and GSH levels were observed in the testes of rats in the GE and GL groups. Also, cytochrome c, caspase 9, and caspase 3 levels in rat testes were significantly lowered in the GE and GL groups when compared to the DA group. Furthermore, testosterone levels in the plasma and testes of rats in the GE and GL groups were significantly (p<0.05) increased in the treated groups when compared to the DA group. The binding affinities of geraniol for 1MAB (-5.4 Kcal/mol) and 5DF4 (-6.1 Kcal/mol) were comparable to that of glibenclamide (-5.5 Kcal/mol; -7.5 Kcal/mol, respectively). Conclusion: This study shows that geraniol has the potential to ebb testicular damage in diabetic rats through the inhibition of oxidative stress, caspase activation, rat liver F1-ATPase, and oxidized rat cytochrome c. This study suggests the use of geraniol-rich diet in traditional Chinese medicine.